Avaliação das propriedades de painéis aglomerados produzidos com resíduos de serrarias de nove espécies de madeiras tropicais da Amazônia - Iwakiri, Setsuo (Acta Amazonica, 2020)
This research was developed to evaluate the quality of particleboards manufactured from sawmill waste of nine tropical wood species of Amazônia. The following species were studied: Scleronema micranthum Ducke (Cardeiro), Ecclinusa guianensis Eyma (Caucho), Scleronema sp. (Castanha-de-paca), Copaifera multijuga Hayne (Copaíba), Ocotea sp. (Louro), Ocotea guianensis Aubl (Louro-espinho), Caryocar villosum Pers. (Piquiarana), Couratari oblongifolia (Tauari) e Virola surinamensis Rol. Warb (Virola). The experimental boards were manufactured with the nominal density of 0.75 g.cm-3, using the urea-formaldehyde resin in the proportion of 8% of solid content based on oven dried wood particles. The boards were pressed at the specific pressure of 40 kgf/cm², temperature of 160 ºC and press time of eight minutes. The evaluations of test results obtained in this study indicate the potential use of the nine species from Amazon rainforest in the production of particleboard, highlighting Ecclinusa guianensis (Caucho) that, in general, showed better results of physical and mechanical properties.